Synthesis of 7-Aryl-3H-[1,2,4]triazolo[3,1-i]purines from 1-Amino-9-aryl-6-iminopurines - Yahyazadeh, Asieh (Asian Journal of Chemistry, 2016)
The tile compounds have been prepared in high yield from 9-aryl-6-iminopurine derivative by reaction with diethoxymethyl acetate.